(untitled) (Research, Society and Development, 2020)
Introduction: Dyspareunia is one of the existing sexual dysfunctions, it is defined as a painful sexual act or attempt. This dysfunction causes severe pain and is classified among the group of painful sexual disorder, which is a highly prevalent category and has a major negative impact on the quality of life of the women affected and their sexual partnership. Objective: To analyze and describe the light of current literature with a good methodological quality, the approach of physiotherapy in the treatment of female dyspareunia. Methodology: This is an integrative literature review with a qualitative and quantitative approach. Studies addressing physical therapy treatment in women with dyspareunia, published from 2010 to 2020, without linguistic restriction, including periodicals, were included. Duplicate studies, book chapters, literature reviews, systematic reviews, editorial letters, comments, guidelines and abstracts of scientific articles were excluded. The databases used for the bibliographic survey were: Pubmed, Medline, PEDro and ScienceDirect. Data collection was carried out in the months of May and July of the current year 2020. Results and Discussion: After collecting the data, it was observed that physiotherapeutic resources such as Electrotherapy and Kinesiotherapy of the pelvic floor have a positive effect regarding this dysfunction, such as in the normalization of muscle tone, in the increase of perineal awareness, in proprioception, in the strengthening, elasticity, vascularization and improvement of pain, thus improving the sexual interaction of women. Final Considerations: It is believed that this study contributes to a possible adaptation of therapeutic services and expansion of knowledge about women’s pelvic sexual pain, we show that the physiotherapist is the health professional who has all the knowledge to provide support to women in this touching.